Cisplatin Neurotoxicity Targets Specific Subpopulations and K+ Channels in Tyrosine-Hydroxylase Positive Dorsal Root Ganglia Neurons - Finno, Carrie J.; Chen, Yingying; Park, Seojin; Lee, Jeong Han; Perez-Flores, Maria Cristina; Choi, Jinsil; Yamoah, Ebenezer N. (Frontiers in Cellular Neuroscience, 2022)
Among the features of cisplatin chemotherapy-induced peripheral neuropathy are chronic pain and innocuous mechanical hypersensitivity. The complete etiology of the latter remains unknown. Here, we show that cisplatin targets a heterogeneous population of tyrosine hydroxylase-positive (TH+) primary afferent dorsal root ganglion neurons (DRGNs) within the primary afferent dorsal root ganglia in mice, determined using single-cell transcriptome and electrophysiological analyses. TH+ DRGNs regulate innocuous mechanical sensation through C-low threshold mechanoreceptors. A differential assessment of wild-type and vitamin E deficient TH+ DRGNs revealed heterogeneity and specific functional phenotypes. The TH+ DRGNs comprise; fast-adapting eliciting one action potential (AP; 1-AP), moderately-adapting ( 2-APs), in responses to square-pulse current injection, and spontaneously active (SA). Cisplatin increased the input resistance and AP frequency but reduced the temporal coding feature of 1-AP and  2-APs neurons. By contrast, cisplatin has no measurable effect on the SA neurons. Vitamin E reduced the cisplatin-mediated increased excitability but did not improve the TH+ neuron temporal coding properties. Cisplatin mediates its effect by targeting outward K+ current, likely carried by through K2P18.1 (Kcnk18), discovered through the differential transcriptome studies and heterologous expression. Studies show a potential new cellular target for chemotherapy-induced peripheral neuropathy and implicate the possible neuroprotective effects of vitamin E in cisplatin chemotherapy.